The Physicochemical Characteristics of Crude Oil Extract Spirulina sp. by Osmotic-Shock Extraction Method - Djamaludin, Heder; Chamidah, Anies (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Spirulina sp. is a potential microalgae. One of the potentials that continue to be developed, such as edible oil. Various extraction methods can obtain Spirulina oil content, i.e., the osmotic shock method as a green extraction method. Each method used can affect the fatty acid components. Not many studies have reported the physicochemical characteristics of oil extract Spirulina using the osmotic-shock method. This study analyzes the physicochemical characteristics of crude oil extract Spirulina sp. extracted using the osmotic-shock method. The study used a simple, completely randomized design with treatment extraction times of 60, 90, and 120 minutes. The data were analyzed using analysis of variance and Duncan's test (α5%). The results showed that the treatment level of 60 minutes produced the lowest physicochemical characteristics and met the International Fish Oil Standards, where peroxide value 1.49±0.0089 mEq/Kg, iodine value 71.37±0.0035 g I2/g, saponification value 502.69±0.0069 mg KOH/g, acid value 0.049±0.0011 mg KOH/g, and Free Fatty Acid 0.0102±0.0003%. The total concentration of Saturated Fatty Acids is 36.18%, monounsaturated fatty Acids 7.72%, and polyunsaturated fatty Acids 49.41%. The fatty acid components are oleic acid/ω-9, linoleic acid/ω-6, linolenic acid/ω-3, eicosapentaenoic acid, and docosahexaenoic acid. The presence of EPA and DHA in the crude oil extract of Spirulina sp. showed potential for development as edible oil. The physical profile of Spirulina sp. oil extract obtained by the osmotic-shock method meets International Fish Oil Standards.